Inventory Control of Twin Tub Washing Machine Spare Parts Using Continuous Review (Q) and Periodic Review (P) Methods - Naila Anargya Fadhillah (Center of Techonolgy (COT), Engineering Faculty, Hasanuddin University, 2026)
In an electronics manufacturing industry, the production process of Twin Tub washing machines has not been operating optimally due to an imbalance between the quantity of purchased and required raw materials, namely spin motors, wash motors, v-belts, and water inlets. This condition makes it difficult for the company to determine the appropriate order quantity. This issue may negatively affect production continuity and increase total inventory costs due to shortages and overstocking of raw materials. Therefore, this study aims to control raw material inventory for twin tub washing machines in order to minimize total inventory costs. This study employs the Continuous Review (Q) Lost Sales and Periodic Review (P) Lost Sales methods. The results show that the Continuous Review (Q) Lost Sales method yields a total cost of IDR 2.735.326.321, which is lower than the Periodic Review (P) Lost Sales method with a total cost of IDR 2.751.408.021. Therefore, the Continuous Review (Q) Lost Sales method is selected as it provides the minimum total cost. Compared to the company’s current method, which amounts to IDR 2.796.945.916, this method results in cost savings of up to 2,20%. Thus, the projected total inventory cost for the upcoming period is IDR 2.299.642.132. The application of the Continuous Review (Q) Lost Sales method is proven to minimize total inventory costs while maintaining spare part availability to support sustainable production continuity.